Why Demography Matters (excerpt) - Danny Dorling; Stuart Gitel-Basten (Journal of Economic Sociology, 2022)
Demography is not destiny. As Giacomo Casanova explained over two centuries ago: ‘There is no such thing as destiny. We ourselves shape our own lives.’ Today we are shaping them and our societies more than ever before. Globally, we have never had fewer children per adult: our population is about to stabilize, though we do not know when or at what number, or what will happen after that. It will be the result of billions of very private decisions influenced in turn by multiple events and policies, some more unpredictable than others. More people are moving further around the world than ever before: we too often see that as frightening, rather than as indicating greater freedom. Similarly, we too often lament greater ageing, rather than recognizing it as a tremendous human achievement with numerous benefits to which we must adapt. The Journal of Economic Sociology publishes the chapter eight “Population and Politics,” where the authors discuss the political demography. Here they address eugenics, in both its historical and contemporary manifestations, and then look again at migration and past fertility patterns that may influence it.